The role of story in invocation: reading a collection of stories "Islam in need of hype and preaching" by Muhammad Al-Said Al- Zahiri - Ould Azzaoui, Mokhtar; Bentarya, Omar (Journal of Human Sciences, 2022)
The short story in Algeria, since its appearance at the first leaders of the reformist movement, has taken an invocation reformist approach, social and educational message and a means of defense against the colonialist, for what it is doing to fight Islam and spread suspicions about its sources and doctrines.This is what the study aims to highlight, through reading the collection of stories (Islam in need of hype and preaching) by Muhammad Al-Said Al-Zahiri, who is the first to write and publish his collection of stories aimed at reforming and fighting suspicions raised about the Holy Quran and principles of Islam.This study included three axes: The first axis is the life of Al-Zahiri, the second is a definition of the collection of stories, and the third axis was among the topics included in this collection.